2016
DOI: 10.1017/s0022149x1600064x
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic potential of the immunomodulatory proteins Wuchereria bancrofti L2 and Brugia malayi abundant larval transcript 2 against streptozotocin-induced type 1 diabetes in mice

Abstract: Epidemiological and experimental evidence has supported the concept of using helminths as alternative bio-therapeutic agents in the treatment of type 1 diabetes (T1D). In the current study, two filarial proteins, recombinant Wuchereria bancrofti L2 (rWbL2) and Brugia malayi abundant larval transcript 2 (rBmALT-2) have been investigated, individually and in combination, for their therapeutic potential in streptozotocin (STZ)-induced T1D. The rWbL2 and rBmALT-2 proteins, when administered individually or in comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 45 publications
1
9
0
Order By: Relevance
“…In our study after treatment with rWbL2, increased levels of the expression of anti-inflammatory cytokine IL-10 and decreased levels of expression of proinflammatory cytokines such as IFN-c, TNF-a, IL-6 and IL-17a was found. This protein has already shown to have immunomodulatory activity through alteration of cytokine levels [14]. This study demonstrated that such alteration in cytokine levels might be directly associated with change in gene expression.…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations
“…In our study after treatment with rWbL2, increased levels of the expression of anti-inflammatory cytokine IL-10 and decreased levels of expression of proinflammatory cytokines such as IFN-c, TNF-a, IL-6 and IL-17a was found. This protein has already shown to have immunomodulatory activity through alteration of cytokine levels [14]. This study demonstrated that such alteration in cytokine levels might be directly associated with change in gene expression.…”
Section: Discussionsupporting
confidence: 53%
“…Therefore, this study has been undertaken to assess the preventive effect of a purified secretory filarial protein rWbL2 against inflammatory ulcerative colitis disease. rWbL2 is one of the secretory SXP/RAL family of proteins [14]. Increased rWbL2 specific IgG4 antibody levels was reported in the sera of actively infected individuals (Shivprasad B unpublished data), which is consistently associated with the increased secretion of IL-10 [13].…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…In those patients, the continuous inflammation destroys mucosal epithelia causing chronic stage of UC. Hence, in this study, three selected filarial recombinant molecules (namely rBmCys, rBmALT2 and rWbL2), with pronounced therapeutic effect in various immune‐mediated disorders, were assessed individually or in combinations for their therapeutic activity on chronic colitis.…”
Section: Discussionmentioning
confidence: 99%